Literatur Review: Costumer Experience in Financial Technologi - Ela Elliyana; Puji Hastuti; Moh Sabran A; Abdul Rahman (JURNAL ADMINISTRASI KANTOR, 2022)
This article aimed to review academic research work carried out in the field of financial technology, and to analyze customer experience in the fintech sector. Fintech is a dynamic and innovative field that takes full advantage of advances in information and communication technology. The concept of customer experience was multidimensional, analyzed from multiple perspectives, and with different valence across different industries. Based on a stimulus approach where the customer experience in fintech was the result of customer evaluation of the stimuli proposed by the fintech company. Using equation modeling, articles sourced from journals were taken from the database using Harzing's Publish or Perish (PoP). The results showed that perceived value, customer support, assurance, speed, and perceived company innovation were related to the customer experience at fintech. In turn, the customer experience related to customer loyalty intentions. Keywords: customer experience, customer loyalty, fintech, financial company innovation.